Pyroligneous Acids of Differently Pretreated Hybrid Aspen Biomass: Herbicide and Fungicide Performance - Korkalo, Pasi; Hagner, Marleena; Jänis, Janne; Mäkinen, Marko; Kaseva, Janne; Lassi, Ulla; Rasa, Kimmo; Jyske, Tuula (Frontiers in Chemistry, 2022)
Pyroligneous acids (PAs) of woody biomass produced by torrefaction have pesticidal properties. Thus, PAs are potential alternative to synthetic plant protection chemicals. Although woody biomass is a renewable feedstock, its use must be efficient. The efficiency of biomass utilization can be improved by applying a cascading use principle. This study is novel, because we evaluate for the first time the pesticidal potential of PAs derived from the bark of hybrid aspen (Populus tremula L. × p. tremuloides Michx.) and examine simultaneously, how production of the PAs can be interlinked with the cascade processing of hybrid aspen biomass. Hybrid aspen bark contains valuable extractives that can be separated before the hemicellulose is thermochemically converted into plant protection chemicals. We developed a cascade processing scheme, where these extractives were first extracted from the bark with hot water (HWE), or with hot water and alkaline alcohol (HWE+AAE), prior its conversion into PAs by torrefaction. The herbicidal performances of PAs were tested using Brassica rapa as test species, and the fungicidal performances was proved using Fusarium culmorum. The pesticidal activities were compared to the PAs of debarked wood, and to the commercial pesticides. According to the results, extractives can be separated from the bark without overtly diminishing the weed and fungal growth inhibitor performances of the produced PAs. The HWE of the bark before its conversion into PAs appeared to have an enhancing effect on the herbicidal activities. In contrast, HWE+AAE lowered the growth inhibition performance of PAs against both the weeds and fungi. The study shows that hybrid aspen is a viable feedstock for the production of herbicidal and fungicidal active chemicals, and it is possible to utilize biomass in according to the cascading use principle.